Specific modes of exercise to improve rotator cuff-related shoulder pain: systematic review and meta-analysis - Wu, Dianxuan; Wen, Zhicheng; Ke, Haolin; Zhang, Jiexin; Zhong, Shaozi; Teng, Jiachen; Xu, Lan; Li, Jintao; Shao, Yan; Zeng, Chun (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveTo investigate the effect of specific modes of exercise on rotator cuff-related shoulder pain (RCRSP) patients, aiming to provide a theoretical reference for conservative treatment and exercise prescription.MethodsData sources included PubMed/MEDLINE, Web of Science, ScienceDirect, and CNKI, covering studies from database inception to June 2024. Study selection followed pre-set inclusion/exclusion criteria. Cochrane methods guided quality assessment and data extraction. Outcome measures included VAS, CMS, and DASH scores. Publication bias assessed via funnel plots; forest plots created using RevMan 5.4.Results13 studies (n = 690) met inclusion criteria for RCRSP exercise interventions. It is indicated that: (1) specific exercises led to modest improvements in performance of pain (SMD = −0.31, 95% CI: 0.46 to −0.16, P < 0.0001) and function, with enhancements in CMS (SMD = 0.59, 95% CI: 0.44 to 0.74, P < 0.00001) and DASH (SMD = −0.60, 95% CI: 0.80 to −0.39, P < 0.00001). (2) Interventions lasting less than 2 months were slightly more effective than those lasting 2 months or longer, observed in VAS (SMD = −0.35, 95% CI: 0.56 to −0.15, P = 0.0007), CMS (SMD = 0.71, 95% CI: 0.47 to 0.96, P < 0.00001), and DASH (SMD = −0.71, 95% CI: 0.99 to −0.43, P < 0.00001). (3) Subgroup analyses revealed that handgrip strength exercises enhanced shoulder pain relief, shoulder mobilization/stretching improved both function and pain levels over 2 months, scapular stabilization exercise improved pain and DASH performance over 2 months, eccentric exercises boosted CMS and DASH performance over 2 months, while proprioceptive exercises showed no significant improvement in pain or CMS performance.ConclusionCompared to non-specific exercises, specific exercise programs moderately alleviate RCRSP symptoms, with shorter interventions (<2 months) demonstrating marginally superior outcomes. Efficacy varies by exercise type, emphasizing the need for individualized prescriptions.Systematic Review RegistrationPROSPERO (CRD42024550602).